Development of Contextual Teaching and Learning-Based Test Instruments to Improve 21st Century Skills in Students - Atika Ulya Akmal; Festiyed (Postgraduate, University of Mataram, 2023)
The purpose of this study was to develop a test instrument for the basic physics concept course which was compiled based on the CTL learning model to improve students' 21st century skills (4C). This type of research is R&D and the design used by ADDIE. The subjects of this study were 25 semester 1 PGSD UNP students who worked on 33 questions on the instrument. The data analysis technique used is quantitative analysis by calculating the validity, reliability of the questions, discriminating power and level of difficulty. The results of this study were 78% valid questions and 22% invalid questions. Reliability of 0.933 which is included in the high reliability category. It is known that 18% of the questions are in the difficult category, 61% are in the medium category and 21% are in the easy category. The power of difference test obtained 6% of the questions included in the very bad category, 3% of the questions included in the bad category, 27% in the sufficient category, 61% in the good category and 3% in the very good category.